Prognostic Implications and Immune Infiltration Characteristics of Chromosomal Instability-Related Dysregulated CeRNA in Lung Adenocarcinoma - Guo, Shengnan; Li, Tianhao; Xu, Dahua; Xu, Jiankai; Wang, Hong; Li, Jian; Bi, Xiaoman; Cao, Meng; Xu, Zhizhou; Xia, Qianfeng; Cui, Ying; Li, Kongning (Frontiers in Molecular Biosciences, 2022)
An accumulating body of research indicates that long-noncoding RNAs (lncRNAs) regulate the target genes act as competitive endogenous RNAs (ceRNAs) playing an indispensable role in lung adenocarcinoma (LUAD). LUAD is frequently accompanied by the feature of chromosomal instability (CIN), however, CIN-related ceRNAs have not yet been investigated. We systematically analyzed and integrated CIN-related dysregulated ceRNAs characteristics in LUAD samples for the first time. In TCGA LUAD cohort, CIN in tumor samples was significantly higher than those of adjacent, and patients with high CIN risk tended to have worse clinical outcomes. We constructed a double-weighted CIN-related dysregulated ceRNA network, in where edge weight and node weight represented the disorder extent of ceRNA and the correlation of RNA expression level and prognosis, respectively. After module mining and analysis, a potential prognostic biomarker composed of 12 RNAs (8 mRNAs and 4 lncRNAs) named CIN-related dysregulated ceRNAs (CRDC) was obtained. CRDC risk score had a positive relation with clinical stage and CIN, and patients with high CRDC risk scores exhibited poor prognosis. Moreover, CRDC tended to be an independent risk factor with high robustness to overcome the effect of multicollinearity among other explanatory variables for Disease-Specific Survival (DSS) in TCGA and two GEO cohorts. The result of functional analysis indicated that CRDC is involved in multiple cancer progresses, especially immune-related pathways. The lower CRDC risk group had higher B cell, T cell CD4+, T cell CD8+, neutrophil, macrophage and myeloid dendritic cell infiltration compared to the patients with higher CRDC risk. Meanwhile, patients with lower CRDC risk could get more benefits from immunological therapy. The results suggested that the CRDC could be a potential prognostic biomarker and an immunotherapy predictor for lung adenocarcinoma.